Vulnerability Assessment with Network-Based Scanner Method for Improving Website Security - Dewi Laksmiati (Information Technology and Science (ITScience), 2023)
The digital world has seen a significant increase in security threats in recent years, with hacker attacks on websites being a major concern in cybersecurity. One platform that is particularly vulnerable is WordPress, which is widely used and therefore a popular target for hackers. About 95.62% hacked website in 2021 is WordPress based site. Therefore, to improve website security we conducted a vulnerability assessment on a WordPress based website, in order to identify vulnerabilities that may be exploited by hackers. To do the vulnerability assessment, we used the network-based scanner based to detect vulnerabilities on the WordPress website. Our results showed that the website had several vulnerabilities that needed to be addressed and fixed immediately. The conclusion of our research highlights the importance of conducting regular vulnerability assessments on WordPress-based websites to reduce the risk of vulnerabilities being exploited. By taking proactive measures to identify and fix vulnerabilities, website owners can better protect their sites from potential hacker attacks. It is crucial for website owners to be aware of the risks posed by security threats in the digital world and to take steps to mitigate these risks to protect their businesses and their customers.